Common and specific neural correlates underlying the spatial congruency effect induced by the egocentric and allocentric reference frame. Issue 4 (5th January 2017) - Liu, Nan; Li, Hui; Su, Wen; Chen, Qi
Abstract: The spatial location of an object can be represented in two frames of reference: egocentric (relative to the observer's body or body parts) and allocentric (relative to another object independent of the observer). The object positions relative to the two frames can be either congruent (e.g., both left or both right) or incongruent (e.g., one left and one right). Most of the previous studies, however, did not discriminate between the two types of spatial conflicts. To investigate the common and specific neural mechanisms underlying the spatial congruency effect induced by the two reference frames, we adopted a 3 (type of task: allocentric, egocentric, and color) × 2 (spatial congruency: congruent vs. incongruent) within‐subject design in this fMRI study. The spatial congruency effect in the allocentric task was induced by the task‐irrelevant egocentric representations, and vice versa in the egocentric task. The nonspatial color task was introduced to control for the differences in bottom‐up stimuli between the congruent and incongruent conditions. Behaviorally, significant spatial congruency effect was revealed in both the egocentric and allocentric task. Neurally, the dorsal‐medial visuoparietal stream was commonly involved in the spatial congruency effect induced by the task‐irrelevant egocentric and allocentric representations. The right superior parietal cortex and the right precentral gyrus were specifically involved in the spatial congruency effect induced by the irrelevant egocentric and allocentric representations, respectively. Taken together, these results suggested that different subregions in the parieto‐frontal network played different functional roles in the spatial interaction between the egocentric and allocentric reference frame. Hum Brain Mapp 38:2112–2127, 2017 . ©2017 Wiley Periodicals, Inc.